Transcriptome Analysis and Identification of the Cholesterol Side Chain Cleavage Enzyme BbgCYP11A1 From Bufo bufo gargarizans - Li, Guangli; An, Tianyue; Li, Yu; Yue, Jinyang; Huang, Ruoshi; Huang, Jia; Liang, Jincai; Yao, Wei; Huang, Liufang; Chen, Yidu; Zhang, Rongrong; Ji, Aijia; et al. (Frontiers in Genetics, 2022)
Bufo bufo gargarizans Cantor are important animal medicine materials in traditional Chinese medicine (TCM). The major pharmacological components bufadienolides from venomous secretion of B. bufo gargarizans are one type of cardiac aglycone with six-member lactone ring and have properties of anti-tumor, cardiotonic, tonsillitis, and anti-inflammatory. The biosynthesis of bufadienolides are complex and unclear. This study explored transcriptome of three different tissues (skin glands, venom glands and muscle) of B. bufo gargarizans by high-throughput sequencing. According to the gene tissues-specific expression profile, 389 candidate genes were predicted possibly to involve in the bufadienolides biosynthesis pathway. Then, a key cholesterol side chain cleavage enzyme BbgCYP11A1 from B. bufo gargarizans was firstly verified in a yeast expression system, and the catalytic activity of BbgCYP11A1 was studied with various redox partners. Interestingly, a plant NADPH-cytochrome P450 reductase (CPR) from Anemarrhena asphodeloides showed notable higher production than BbgAdx-BbgAdR-1 from B. bufo gargarizans. There results will benefit the biosynthesis pathway of bufadienolides in B. bufo gargarizans.